Strengthening urban primary health care in India: a critical appraisal of evolving service delivery models - Shrivastava, Smita; Choudhary, Annu; Gopal, K. Madan (International Journal Of Community Medicine And Public Health, 2025)
Urban India is facing a growing burden of non-communicable diseases, migration-linked vulnerabilities, and overdependence on tertiary care. While the National Urban Health Mission (NUHM) was launched to strengthen urban primary health care, its implementation has varied across states. This review presents a critical appraisal of evolving urban PHC models such as Delhi’s Mohalla Clinics, Hyderabad’s Basti Dawakhanas, Maharashtra’s Aapla Dawakhana, Karnataka’s Namma Clinics and Rajasthan’s Janta clinic. This review presents a comparative analysis of five state-led urban PHC models implemented between 2015 and 2023. Data sources included official implementation guidelines, state reports, NHSRC best practice compendia, and peer-reviewed articles. The models were selected based on visibility in policy discourse, geographic representation, and documented field experience under the NUHM framework. The analysis highlights key gaps in staffing, digital infrastructure, governance, and alignment with Indian Public Health Standards (IPHS). While some models offer promising examples of decentralized, community-responsive care, they remain limited in scope, scalability, and integration with existing health systems. Most facilities suffer from inadequate infrastructure, fragmented referral linkages, and a lack of standardized human resource norms. The paper recommends a harmonized urban PHC strategy anchored in IPHS, a dedicated HR policy for urban areas, digital health integration, and financial sustainability mechanisms. A renewed focus on equity, digital readiness, and convergence with urban development and social protection schemes is essential to make UPHCs the first point of contact for urban populations. This review highlights key enablers for strengthening UPHCs as the cornerstone of India’s urban health system.